Flexible carbon nanofiber film with diatomic Fe-Co sites for efficient oxygen reduction and evolution reactions in wearable zinc-air batteries - Wang, Yiyan; Li, Zongge; Zhang, Peng; Pan, Yuan; Zhang, Ying; Cai, Qiong; Silva, S. Ravi P.; Liu, Jian; Zhang, Guoxin; Sun, Xiaoming; Yan, Zifeng (Nano energy, 2021)
Carbon nanofiber (CNF) papers have been widely used in many renewable energy systems, and the development of its catalytic function is of great significance and a major challenge. In this work, we pioneer a time- and cost-efficient strategy for the preparation of large-area flexible CNF films with uniformly distributed diatomic FeN3-CoN3 sites (Fe1Co1-CNF). Due to the excellent compatibility and similar functionality of the pre-designed ZnFeCo-NC precursors (ZnFeCo-pre) with the electrospun polymer polyacrylonitrile (PAN), the mixture of ZnFeCo-pre and PAN can be co-electrospun and subject to a standard CNF fabrication process. The resulting Fe1Co1-CNF exhibits excellent bifunctional catalytic performance for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), attributing to the abundant dual catalytic FeN3-CoN3 sites which are mutually beneficial for attaining optimal electronic properties for the adsorption/desorption of reaction intermediates. The assembled liquid-electrolyte ZAB provides a high specific power of 201.7 mW cm−2 and excellent cycling stability. More importantly, due to the good mechanical strength and flexibility of Fe1Co1-CNF, portable ZAB with exceptional shape deformability and stability can be demonstrated, in which Fe1Co1-CNF utility as an integrated free-standing membrane electrode. These findings provide a facile strategy for manufacturing flexible multi-functional catalytic electrodes with high production. [Display omitted] •Large-area self-standing flexible CNF film with diatomic Fe-Co sites was developed.•The diatomic Fe-Co sites render optimized adsorption of O-containing intermediates.•The Fe1Co1-CNF exhibits superior bifunctional ORR/OER performance.•The Fe1Co1-CNF shows great potential in liquid/flexible Zn-air battery.